Kepemimpinan Camat Sebagai Faktor Penentu Partisipasi Masyarakat Dalam Pembangunan di Kecamatan Kema Kabupaten Minahasa Utara - Lengkong, Florence Daicy Jetty; Pangkey, Masye S (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The purpose of this research is to explain the efect leadership of the Head of Kema sub district to the citizen participation. This research was conducted in the Kema sub district with 30 respondents sample. It used purposive sampling technique and stratified random sampling. Data was collected by using questionnaire technique in the form of questions measured by Likert scale. The analysis method used here is descriptive analysis and simple regression analysis. Data analysis was conducted by using SPSS version 12,0 computer program. The results of this research indicated that: (1) based on the descriptive analysis shown that the leaderships of the Head of Kema sub district and the citizen participation both are high category. (2) based on the simple regression analysis shown the efect leadership of the Head of Kema sub district to citizen participation is positive and significant. Based on this research may suggestion to the Head of Kema sub district that to increase the citizen partisipation, must be used leadership models. Keywords: leadership of the Head of Kema sub district, citizen partisipation.